Analisis Kinerja Keuangan Bank BNI Dan Bank Muamalat Sebelum Dan Selama Pandemi Covid-19 - Virna, Marlinda Intan; Maulana, Zefri; Tajul ‘Ula, Tajul; Andrini, Rozi (MUI Kota Pekanbaru, 2024)
The coronavirus pandemic means the banking sector cannot freely distribute credit. This is due to the increasing risk of failure to pay creditors because the majority of people, both individuals and companies, tend to experience a decrease in income during the Corona virus pandemic. This research aims to compare differences in the performance developments of Bank BNI and Bank Muamalat in several months in the period before and during the Covid-19 pandemic. This research is quantitative research. The population and sample in this research are Bank Muamalat and Bank BNI which have annual financial reports and quarterly reports that have been officially published and the samples used are 26 samples in the 2017-2023 period. The data collection technique used is secondary data. The data analysis technique used is a parametric test, non-parametric analysis. The research results show that in terms of financial performance ratios ROA, LDR and BOPO, BNI bank has superior performance compared to Muamalat bank both before and during Covid-19. Different from the CAR ratio, Bank Muamalat has sufficient capital to accommodate the risk of loss better than Bank BNI. Furthermore, regarding the NPL ratio, both before and during Covid-19, Muamalat Bank had a higher risk of credit problems compared to BNI Bank.